A multi-dimensional analysis of integrated farming system in salt-affected ecologies - RAJKUMAR; KUMAR, SURESH; FAGODIYA, RAM KISHOR; SINGH, AWTAR; SHEORAN, PARVENDER; YADAV, GAJENDER; SINGH, NIRMAL; MANDAL, SUBHASIS; YADAV, R K (The Indian Journal of Agricultural Sciences, 2025)
The horizontal expansion of the arable areas seems infeasible with dwindling natural resources and declining the average size of landholdings. For harnessing the economic, environmental and social benefits of vertical expansion, the Integrated Farming Systems (IFS) could be instrumental in sustaining the livelihood security of the resource-poor farmers dwelling in the degraded areas. An IFS model of 2 ha was designed covering three major components, namely, grain, horticultural crops and subsidiary at ICAR-Central Soil Salinity Research Institute, Karnal and data from the year 2021–23 was considered for present study. A multi-dimensional analysis covering the financial (net present value, benefit: cost ratio and internal rate of return), soil health (total organic carbon and nitrogen) and environmental (carbon sequestration and greenhouse gas emission) parameters was carried out of an IFS model developed by ICAR- Central Soil Salinity Research Institute, Karnal, Haryana. The findings showed that IFS generates more net return i.e., Rs 66596 than conventional rice-wheat system of equivalent scale (2.0 ha). Additionally, along with improved soil health, the IFS generated lesser ( 13.25%) GHG emission as compared to the conventional rice-wheat system. To enhance carbon sequestration in the Integrated Farming System (IFS), more perennial trees should be planted in underutilized areas, especially along boundaries. This is vital for achieving net-zero emissions. Despite its financial viability and environmental benefits, the IFS has low adoption rates. Financial assessments show that economic incentives for initial investments are necessary to encourage wider adoption.